Sars-Cov-2 Humoral Immune Response in Patients with Cardiovascular Risk Factors: The Community Cohort Study Protocol - Navarrete-Couble, M; Bachelet-Norelli, V; Silva-Ayarza, I; Lizana-Montecinos, F; Gomolan-Gonzalez, P (BMJ Publishing Group, 2022)
Introduction The COmmunity Cohort Study aims to determine, after natural exposure to SARS-CoV-2 or anti-SARS-CoV-2 vaccines deployed in Chile to prevent COVID-19 in the context of the current pandemic, the strength and duration of detectable neutralising antibodies in adult ambulatory primary care patients with cardiovascular risk factors. Methods and analysis We will set up a community-based longitudinal, prospective cohort study. The study will be conducted in two public outpatient clinics located in the southern district of Santiago, Chile. We expect to begin recruitment in the second quarter of 2022. Each patient will be followed up for at least 1 year after inclusion in the cohort. The eligible population will be adult patients registered in the Cardiovascular Health Programme. Exposure in this study is defined as any event where participants have contact with SARS-CoV-2 antigens from natural exposure or vaccination. The primary outcomes are seroconversion and strength and duration of the neutralising IgG antibodies to SARS-CoV-2. Secondary outcomes are any COVID-19-related event or intercurrent morbidities or death. Data will be collected by extracting serial blood samples and administering a questionnaire at the first face-to-face contact and monthly follow-up time points. The sample size estimated for this study is 1060. We will characterise the cohort, determine the seroprevalence rate of neutralising antibodies at baseline and determine the rates of antibody decline using a longitudinal mixed-effects model. Ethics and dissemination The Scientific Ethics Committee of the South Metropolitan Health Care Service approved the study protocol (Memorandum No 191/2021). We will present the results in two peer-reviewed publications and national and international professional and academic meetings. We will organise seminars with relevant stakeholders and hold town hall meetings with the local community. We will set up a COmmunity Cohort Study website at www.communitystudy.cl to disseminate the study purpose, research team and milestones. © 2022 Author(s) (or their employer(s)). Re-use permitted under CC BY-NC. No commercial re-use. See rights and permissions. Published by BMJ.